How Canada Compares: Engagement of Seniors in Chronic Condition Management in 11 Countries - Grace Cheung, Patricia Sidhom and Katerina Gapanenko (Healthcare Quarterly, 2018)
Patient engagement is a growing movement that emphasizes the collaboration between patients and their healthcare providers. Patient engagement in chronic condition management is important because its success relies on patients preventing and acting on symptoms outside of their doctor's office. For many chronic conditions, seniors are often affected more than other age groups. Here we highlight how Canadian seniors are engaged in their management of chronic conditions compared to seniors in 10 peer countries. Although more Canadian seniors reported feeling engaged by their regular doctors than the international average, there is room for improvement.
Keywords: seniors care, primary care, self-managed care